Open Online Course on Basic Cardiopulmonary Resuscitation: Investigation of an Audience and the Effects of Distant Training - A. A. Birkun; V. R. Dantanarayana (Общая реаниматология, 2020)
Aim. To study the demand for the massive open online course on basic cardiopulmonary resuscitation (CPR), and to evaluate effects of the training based on the socio-demographic profile of the audience.Material and methods. The data obtained from a survey conducted on participants of the online course «First Aid in Cardiac Arrest (Basic Resuscitation)» during a one-year period (07.2018–07.2019) were analyzed, including demographic data, initial and final levels of knowledge on CPR, and willingness to resuscitate a stranger. The 5-point Lickert scale was used for self-assessment of knowledge and willingness to attempt CPR.Results. The analysis includes data collected from 11,924 people, out of which 3,445 (29%) have completed the training. Eighty percent of participants live in the Russian Federation. The mean age of trainees, who completed the course, was 25.7 years, 45% of them were males, 42% had learnt CPR previously, 12% had medical education. As a result of the training, a significant increase (P<0.001) in the willingness to attempt CPR (from 3.26 to 4.16 points) and an increase in self-perceived CPR knowledge (from 2.24 to 3.98 points) were registered. The percentage of trainees who expressed a high level of willingness to perform CPR (4–5 points) increased from 44% to 81% (P<0.001). The course was more likely to be completed by those trainees who had previous training in CPR (p<0.001), who initially demonstrated higher willingness to provide CPR (P=0.003) or a higher level of knowledge in CPR (P<0.001). Trainees who had previous CPR training showed a much higher level of knowledge, higher self-confidence and a higher level of readiness to provide CPR (P<0.001). Approximately 14% of trainees with medical education reported having no previous training in CPR.Conclusions. The massive open online course promotes knowledge of CPR and serves as an important tool for increasing the willingness of lay people to provide first aid in case of cardiac arrest. Previous CPR training is a motivating factor to continue education in resuscitation.